The Result Model of Career Promotion Activities in Home Economics for the Elderly in Local Administrative Organization, Phitsanulok Province - Sukprasert, Jirapha; Kaewsritong, Jiraphat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
The purpose of this study is to examine the impact of implementing the model of Home Economics career promotion activities for the elderly in local administrative organizations of Phitsanulok Province. It was an experimental study with a one group pretest-posttest design. The sample group consisted of 80 elders, aged 60 to 79, from the Plai Chumphon Elderly School in the Mueang District of Phitsanulok Province. The sample size was determined by following Craigie and Morgan's table and then simply picked at random using a lotto and according to the established parameters. The tools used include the model of activities for promoting careers in Home Economics for the elderly, a knowledge assessment, an occupational skills assessment and a satisfaction questionnaire. Data were analyzed using descriptive statistics and inferential statistics. The investigation revealed a statistically significant difference between the elderly's knowledge test scores before and after comparison at the 0.05 level. The maximum value of satisfaction was =4.58, S.D. = 0.23.